Influence of the upper gravity-wave damping layer on precipitation over complex terrain - Duan, H. X.; Zhang, T. J.; Gong, C. S.; Zhou, G. L.; Zhu, WeiWei (Frontiers in Environmental Science, 2022)
The upper boundary condition of a numerical model can significantly influence the model prediction results. This study used the Weather Research and Forecasting (WRF) model to introduce the Rayleigh damping layer in the complex terrain of southern Gansu, China. Sensitivity TESTs of a strong precipitation process in 2018 are conducted, and the effects of the upper gravity-wave absorbing layer and vertical velocity damping term of different schemes are explored, which can effectively reduce the error caused by false gravity waves in the complex terrain in southern Gansu Province. Moreover, the applicability of this model in the complex terrain of northwestern China is discussed. Prediction of the precipitation area and intensity is improved. Specifically, the introduction of an implicit gravity-wave damping layer has a more significant damping effect on the upwardly propagating gravity-wave.